Building colleges for the future: pedagogical and ideological spaces. Issue 6 (2nd November 2017) - Smith, Rob
Abstract: This article focuses on the Building Colleges for the Future (BCF) initiative (2008) which saw a wave of new-build Further Education (FE) colleges spring up across England in the final years of the New Labour government. It draws on qualitative data from a research study focusing on four new-build colleges in the West Midlands of England to theorise the BCF initiative. Using theory derived primarily from Lefebvre, the paper contextualises BCF within a frame of neoliberalisation and discusses the impact of the 'production of space' represented by the initiative with a research focus on two areas: pedagogy and ideology. The main findings are that these new-build colleges can be interpreted as spatial expressions of policy-makers and others' perceptions of teaching and learning; in ideological terms, they also trumpet a 'new lifestyle' and a 'new art of living' for FE staff and students that is however, in tension with residual pedagogical practices and values. The article concludes that despite being an expression of neoliberal abstract space, these new-builds can still be seen as providing a frame for alternative individual and collective encounters with education which may subvert and outlast the processes of neoliberalisation that they appear to embody.